2011
DOI: 10.1093/ibd/17.supplement1.s13a
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1-induced intestinal alkaline phosphatase promotes resolution of inflammation through LPS detoxification.

Abstract: Inflammatory bowel diseases are disorders of unknown etiology characterized by inappropriate inflammation. There is recent intense interest in understanding mechanisms of inflammatory resolution. Resolvin‐E1 (RvE1) has been demonstrated to promote resolution in numerous disease models. Given the importance of epithelial cells in coordinating mucosal inflammation, we hypothesized that RvE1 elicits an epithelial inflammatory resolution signature. Microarray profiling of epithelial cells exposed to RvE1, revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 0 publications
0
50
5
Order By: Relevance
“…Previous work showed that oral L-Phe inhibited IAP activity and increased the severity of experimental colitis (39). In mice treated with L-Phe there was not a significant change in permeability in either WT or CF mice (Fig.6).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous work showed that oral L-Phe inhibited IAP activity and increased the severity of experimental colitis (39). In mice treated with L-Phe there was not a significant change in permeability in either WT or CF mice (Fig.6).…”
Section: Resultsmentioning
confidence: 96%
“…To address this we used the IAP inhibitor L-Phe, added to the liquid diet. Previous work showed that oral L-Phe increased passage of gavaged LPS into blood in rats (56) and increased the severity of experimental colitis induced with dextran sodium sulfate in mice (39). When we treated mice with oral LPhe, intestinal permeability was not affected in either WT or CF mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both 18 R and 18 S enantiomers of RvE1 are ligands for ChemR23 and BLT1 G protein-coupled receptors 29. RvE1 has been shown to induce expression of intestinal alkaline phosphatase in human CRC cells in a ChemR23-dependent manner and abrogate chemically induced colitis in mice 34. It is currently not known whether ω-3 PUFA-derived resolvins exhibit antineoplastic activity.…”
Section: Mechanisms Of the Antineoplastic Activity Of ω-3 Pufasmentioning
confidence: 99%
“…Another example indicating that AP is regulated by dietary lipids is that cod liver oil rich in n-3 fatty acid has been shown to increase the secretion of intestinal AP (Kaur et al, 2007). Interestingly, this may be explained by the increased expression resolvin-El, an antiinflammatory n-3 fatty acid lipid mediator, which induces AP activity (Campbell et al, 2010). Furthermore, increased dietary fat consumption reduces intestinal AP activity in obesity-prone rodents (de La Serre et al, 2010).…”
Section: Endotoxin Detoxificationmentioning
confidence: 99%